In Vitro and in Vivo Measurement of Total Antiplasmin Activity - Matsuo, Osamu; Mihara, Hisashi (Thrombosis and Haemostasis, 1977)
Total antiplasmin was measured in vitro and in vivo. In the former case, rabbit plasma was mixed with various concentrations of Urokinase (UK) and the least concentration for appearance of fibrinolytic activity was estimated. This concentration was multiplied by the plasma volume of the rabbit to give the in vitro total antiplasmin. The mean value for 14 rabbits was 4,068.6 units.In order to estimate the total antiplasmin in vivo, UK solution was infused into rabbits. The infusion speed was multiplied by the time of the first appearance of fibrinolytic activity to give the total antiplasmin, although when the infusion speed was low, fibrinolytic activity did not appear during infusion. The mean in vivo total antiplasmin calculated for 6 cases where the infusion speed was high and fibrinolytic activity was observed, was 28,699.8 units, i.e. about 7 (range, 3-11) times the in vitro value.